Influence of virgin coconut oil on the inhibitory effect of emulsion-based edible coatings containing cinnamaldehyde against the growth of Colletotrichum gloeosporioides (Glomerella cingulata). (March 2021) - Permana, Asep Wawan; Sampers, Imca; Van der Meeren, Paul
Abstract: The antifungal activity of emulsion-based edible coatings incorporating cinnamaldehyde against Glomerella cingulata was investigated by determining the effect of virgin coconut oil and oleic acid on the growth rate and its effect on the antifungal effectiveness of cinnamaldehyde using the modified Gompertz model and the minimum inhibitory concentration. The presence of virgin coconut oil, oleic acid and their mixture in emulsions without cinnamaldehyde up to 40% in the growth media showed the ability to slow down the growth rate of the fungi and also to extend the lag phase. However, it could not inhibit the growth of fungi. The slowest growth of fungi was observed from the emulsion containing beeswax, virgin coconut oil, and oleic acid, followed by those containing beeswax-virgin coconut oil. On the other hand, Tween® 80 contributed to promoting the growth rate. The minimum inhibitory concentration of cinnamaldehyde in the emulsions to inhibit the fungal growth was 0.76 mM. The presence of virgin coconut oil in the emulsions did not influence the effectiveness of the antifungal activity of cinnamaldehyde, whereas oleic acid slightly decreased it. The results led to the conclusion that virgin coconut oil is a promising as an alternative ingredient for emulsion-based edible coatings. Highlights: Beeswax, virgin coconut oil, oleic acid & their mixture slow down fungi growth rate. Virgin coconut oil is better at reducing fungi growth rate compared to oleic acid. Minimum concentration of cinnamaldehyde to inhibit Glomerella cingulata is 0.76 mM. Virgin coconut oil is an alternative ingredient for emulsion-based edible coating.